Ours to tell : reclaiming Indigenous stories - Yellowhorn, Eldon, 1956-; Lowinger, Kathy (Annick Press, 2025)
"A wide-ranging anthology that shines a light on untold Indigenous stories as chronicled by Indigenous creators, compiled by the acclaimed team behind Turtle Island and Sky Wolf's Call. For too long, stories and artistic expressions from Indigenous people have been written and recorded by others, not by the individuals who have experienced the events. In Ours to Tell, sixteen Indigenous creators relate traditions, accounts of historical events, and their own lived experiences. Novelists, poets, graphic artists, historians, craftspeople, and mapmakers chronicle stories on the struggles and triumphs lived by Indigenous people, and the impact these stories have had on their culture and history. Some of the profiles included are: Indigenous poet E. Pauline Johnson, acclaimed novelist Tommy Orange, brave warrior Standing Bear, poet and activist Rita Joe. With each profile accompanied by rich visuals, from archival photos to contemporary art, Ours to Tell brilliantly spotlights Indigenous life, past and present, through an Indigenous lens. Because each profile gives an historical and cultural context, what emerges is a history of Indigenous people."--